Development of microencapsulated grape juice powders using black 'Isabel' grape peel pectin and application in jelly formulation with enhanced in vitro bioaccessibility of anthocyanins - Karadag, Ayse; Ozkan, Kubra; Sagdic, Osman (WILEY, 2024)
In this study, pigmented pectin (grape pectin, GP) was extracted from the peels of black Isabel grapes. This highly methoxylated GP was composed mainly of galacturonic acid, arabinose, and other neutral monosaccharides. Its red color was ascribed to the anthocyanin content, and the main contribution was from malvidin-3-O-glucoside. To improve the yield and color properties of spray-dried Isabel grape juice powders, maltodextrin (MD) was substituted with this colored GP. When 25% of MD was substituted with GP, the powder yield increased from 46.0% to 60.4%, but it decreased to 21% when the substitution was 40%. GP inclusion increased the encapsulation efficiency of total anthocyanin in powders from 55.70% to 88.66%. When this spray-dried grape juice powder containing GP was utilized in a jelly recipe (4%-10%), a higher level of inclusion yielded stronger and more brittle jellies. When the jellies containing varying amounts of GP were subjected to in vitro digestion, the formulation with a higher amount of GP yielded a higher recovery of anthocyanins. In addition to being utilized as a carrier agent for spray-drying applications, this pigmented GP can also be tailored for a variety of applications, such as the development of pH-sensitive edible films and functional beverage formulations.
Keywords: anthocyanin; digestion; maltodextrin; pectin; spray-drying; MICROWAVE-ASSISTED EXTRACTION; HEALTH-RELATED COMPOUNDS; PHYSICOCHEMICAL PROPERTIES; ACID-EXTRACTION; APPLE POMACE; OPTIMIZATION; YIELD; STABILITY; VINIFERA; PURITY; Food Science & Technology